Growth mindset in mathematics: A bibliometric analysis - Metu, Chukwuemeka; Marbán, José Maria; Espina, Estefanía (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2025)
A growth mindset is the belief that one's intellect and abilities may develop through effort. This mindset suggests that intelligence is not fixed but adaptable. With the continuous growth in literature on the growth mindset in mathematics, there is a need to investigate the current trends from a bibliometric perspective. To meet this need, the leading countries, source citations, author co-citations, and word co-occurrences were examined. A total of 317 articles were retrieved from the Scopus and Web of Science (WoS) databases spanning 2014–2023. The VOSviewer software was used to analyze the collected data. The United States was the leading contributor to growth mindset research, Frontiers in Psychology emerged as the major source of citations, with Dweck being the most cited author. The word co-occurrence map was grouped into different clusters. The Scopus database shows how belief systems shape mindsets and how motivation intersects with clinical and longitudinal investigations. WoS emphasizes the importance of interventions that narrow belief-achievement gaps, as well as the role of technology. These findings offer valuable insights into the expanding body of research on growth mindset in mathematics, paving the way for further research to explore interventions, cultural influences, and long-term effects on student outcomes.